2016
DOI: 10.2459/jcm.0000000000000207
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coronary artery disease on outcomes after liver transplantation

Abstract: Liver transplantation in patients with CAD is not associated with prohibitive risk for cardiac events and patient mortality. Appropriately treated CAD should therefore not represent a contraindication to liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 42 publications
4
48
2
1
Order By: Relevance
“…The incidence of systolic HF after OLT reported in our study is similar to that reported by others . Qureshi et al reported an incidence of 7% among 970 patients after a median follow‐up of 5 years, a quarter among who developed HF within a week of OLT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The incidence of systolic HF after OLT reported in our study is similar to that reported by others . Qureshi et al reported an incidence of 7% among 970 patients after a median follow‐up of 5 years, a quarter among who developed HF within a week of OLT.…”
Section: Discussionsupporting
confidence: 90%
“…Controls were matched for variables that may independently influence post‐OLT cardiac function, specifically age, gender, and MELD score. A higher MELD score has been shown to be associated with systolic HF after OLT in some studies . As we were looking at transplant recipients over a decade, we also included year of OLT to our matching criteria to account for any change in practice that might have occurred during this period.…”
Section: Methodsmentioning
confidence: 99%
“…13-16 Multi-vessel CAD (versus no CAD) has been associated with increased mortality and postoperative hemodynamic instability even in the absence of severe stenosis, 17 however, recent data has shown that severity or extent of CAD does not impact post-LT survival, if appropriately revascularized. 8,18 …”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Uma justificativa para diferença de resultados pode residir no fato de que nossos pacientes que apresentavam lesão obstrutiva importante foram submetidos previamente a angioplastia coronária havendo, portanto, redução potencial do risco o que não se deu em outros estudos (6,8) . Pesquisa revisando 386 casos consecutivos de transplante hepático constatou também que a mortalidade permaneceu similar independentemente do grau de coronariopatia obstrutiva concluindo que a realização de transplante hepático em pacientes com doença arterial coronária, não se associa com risco proibitivo de eventos cardíacos e mortalidade, uma vez apropriadamente tratados preoperatoriamente (13) .…”
Section: Discussionunclassified